Pengaruh kinerja keuangan terhadap return saham pada perusahaan makanan dan minuman yang terdaftar di Bursa Efek Indonesia pada tahun 2017-2020 - Panggabean, Indah Natasya; Mariska Sisilia, S.E., M.Si (Program Studi Akuntansi IKOPIN, 2022)
The increase in liquidity, solvency and profitability is not always followed by an increase or decrease in stock. The background of this research is the difference between the theoretical basis and the results of previous studies. The purpose of this study was to examine the effect of liquidity, solvency and profitability on stock returns. Data collection techniques using documentation techniques obtained 8 samples from 30 population companies. The conclusion of this study is that stock returns are not influenced by liquidity and solvency. While stock returns are influenced by profitability.